Not as good as it used to be: Do streaming platforms penalize quality? - Jacopo Gambato; Luca Sandrini (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
In this study, we analyze the incentives of a streaming platform to bias consumption when products are vertically differentiated. The platform offers mixed bundles of content to monetize consumer interest in variety and pays royalties to sellers based on the effective consumption of the generated content. When products are not vertically differentiated, the platform has no incentive to bias consumption in equilibrium. With vertical differentiation, royalties can differ, and the platform biases recommendations in favor of the cheapest content, hurting consumers and high-quality sellers. Biased recommendations, if unconstrained, eliminate sellers' incentives to increase the quality of their content, but if constrained, may lead to the inefficient allocation of R&D efforts.
Keywords: D4; L1; L5; 330; platform economics; media economics; content aggregator; recommendation bias; innovation